In situ enzymatic hydrolysis characterisation of phospholipid using 1H NMR in a heterogeneous environment. (1st March 2023) - Wang, Changhao; Li, Yunyan; Lin, Yanqin; Wang, Yonghua; Chen, Zhong; Zhu, Lei; Wang, Junfeng
Abstract: Enzymatic hydrolysis of phospholipids is an important biological event in organisms that is also widely applied in the food industry. In situ nuclear magnetic resonance (NMR) is a powerful non-invasive technique for studying the mechanism of enzymatic reactions. However, their application in phospholipid hydrolysis is limited. In this study, we demonstrated that in a phospholipase A1 (PLA1)-catalysed 1, 2-diacyl-sn-glycero-3-phosphocholine (POPC) hydrolysis system in an aqueous emulsion, the accumulation of POPC hydrolysates caused severe heterogeneity, which significantly reduced the 1 H NMR spectral intensity and resolution. To overcome the sample heterogeneity, we used the intermolecular dipolar-interaction enhanced all lines-II (IDEAL-II) sequence to obtain one-dimensional (1D) high-resolution 1 H intermolecular double quantum coherence (iDQCs) NMR spectra through two-dimensional (2D) acquisition. These spectra enabled us to assign and trace the characteristic peaks of POPC and its hydrolysates in real time. In particular, we performed quantitative estimation of the reaction kinetics based on the g2 and g3 protons and provided direct evidence of the enzymatic hydrolysis process. This study not only fills the gap in 1D 1 H spectrum data of phospholipids and their mixtures with hydrolysates, but also provides an effective method for a comprehensive and rapid analysis of fatty acids and even more complex heterogeneous systems. Graphical abstract: Image 1 Highlights: Enzymatic hydrolysis of POPC in aqueous solution generates heterogeneous products. Using IDEAL-II sequence can obtain high-resolution 1 H iDQCs spectra for POPC hydrolysis. The process of enzymatic POPC hydrolysis is traced and analysed using iDQCs spectra.